The complete mitogenome of the Australian freshwater shrimp Paratya australiensis Kemp, 1917 (Crustacea: Decapoda: Atyidae). (2nd September 2016) - Gan, Huan You; Gan, Han Ming; Lee, Yin Peng; Austin, Christopher M.
Abstract: The mitochondrial genome sequence of the Australian freshwater shrimp, Paratya australiensis, is presented, which is the fourth for genera of the superfamily Atyoidea and the first atyid from the southern hemisphere. The base composition of the P. australiensis, mitogenome is 33.55% for T, 18.24% for C, 35.16% for A, and 13.06% for G, with an AT bias of 71.58%. It has a mitogenome of 15, 990 base pairs comprised of 13 protein-coding, 2 ribosomal subunit and 22 transfer RNAs genes and a non-coding AT-rich region. The mitogenome gene order for the species is typical for atyid shrimps, which conform to the primitive pan crustacean model.